Rows and rows-end border effect at two levels of nitrogen on four cultivars of rice in Southeast Rio Grande do Sul, Brazil - Vernetti, Veronica Peixoto; Vernetti, Francisco de Jesus; Junior, Paulo Silveira (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this research was to determine the occurrence of rows border effect and the extension of rows-end border effect on the yield of four rice cultivars (Oryza sativa L.) grown in the field, at two levels of nitrogen: 30 kg/ha and 60 kg/ha. IAS 12-9 Formosa showed the most outstanding reaction to the different cultivars in border rows, followed by IRGA-408 and EEA-406; Bluebelle was the less sensitive lo border effect. The average yield of the four cultivars in middle rows was statistically greater with 60 kg/ha than with 30 kg/ha of nitrogen when IRGA-408 was at the border rows; conversely, the mean yield was significantly smaller under 60 kg/ha of nitrogen, with EEA-406 at the border rows. As to the rows-end border effect, the results indicated that in the first 0,25 m of every row the higher yields were similar for the four cultivars. However, on IAS 12-9 Formosa, 0,50 m of rows-end trimming is sufficient to remove border effect; for Bluebelle the extension of the rows-end trimming necessary to eliminate that effect could not be clearly established (0,50 m or 0,75 m); on EEA-406 and IRGA-408 there is rows-end border effect up to 0,75 m. Therefore, the use of rows-end trimming in rice yield trial plots is indicated and the extension of the end-trimming should vary according to the cultivar. The rows border effect varied according to the cultivar in the middle rows.